Clinical Trial Designs and Measures in Hereditary Spastic Paraplegias - Trummer, Brian; Haubenberger, Dietrich; Blackstone, Craig (Frontiers in Neurology, 2018)
Hereditary spastic paraplegias (HSPs) are a large group of genetically-diverse neurologic disorders characterized clinically by a common feature of lower extremity spasticity and gait difficulties. Current therapies are predominantly symptomatic, and even then usually provide inadequate relief of symptoms. Going forward, HSP therapeutics development requires a systematic analysis of quantifiable measures and tools to assess treatment response. This review summarizes promising therapeutic targets, assessment measures, and previous clinical trials for the HSPs. Oxidative stress, signaling pathways, microtubule dynamics, and gene rescue/replacement have been proposed as potential treatment targets or modalities. Quantitative evaluation of pre-clinical rodent HSP models emphasize rotarod performance, foot base angle, grip strength, stride length, beam walking, critical speed, and body weight. Clinical measures of HSP in humans include 10-m gait velocity, the Spastic Paraplegia Rating Scale (SPRS), Ashworth Spasticity Scale, Fugl-Myer Scale, timed up-and-go, and the Gillette Functional Assessment Questionnaire. We conducted a broad search for past clinical trials in HSPs and identified clincial trials investigating pharmacological agents including atorvastatin, gabapentin, L-threonine, botulinum toxin, dalfampridine, methylphenidate, and baclofen. We provide recommendations for future HSP treatment directions based on these prior research experiences as well as regulatory insight.